The Influence of Discipline and Teamwork on Employee Work Motivation at the Rasanae Barat District Office - Zaelani, Gufran; Hidayanti, Mawar; Kusumayadin, Firmansyah (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of work discipline and teamwork on employee motivation at the Rasanae Barat District Office. The research employed a quantitative approach using questionnaires distributed to employees as respondents. Data were analyzed using multiple linear regression to determine the relationship and contribution of independent variables to the dependent variable. The results indicate that work discipline and teamwork significantly affect employee motivation, with a contribution rate of 90.4%. These findings highlight that enhancing discipline and team synergy can optimally improve employees’ work motivation. The study also recommends strengthening work regulations, continuous coaching, and developing effective communication and collaboration among employees to foster a professional work culture. Future research is suggested to include additional variables such as leadership, work environment, or compensation to obtain a more comprehensive understanding of factors influencing work motivation.